Brodie’s abscess of proximal shaft radius in 17-year-old male: a case report - Warade, Nikhil R.; Rengerla, Saikrishna B.; Wankhede, Aniket K.; Deshpande, Vyankatesh (International Journal of Research in Orthopaedics, 2022)
Brodies abscess is an uncommon form of osteomyelitis. It is typically found in metaphyseal region of long bones particularly of lower limb. We herein report rare case of Brodies abscess of proximal shaft radius in 17-year-old male presented with pain over proximal aspect of left forearm for 2 months. A plain radiograph showed a translucent lesion of approximately 1.9×1.1 cm. Magnetic resonance imaging (MRI) showed Penumbra sign on T1 and T2 weighted images. Laboratory results showed no inflammatory response. Treatment was done by curettage. Culture report showed Staphylococcus aureus growth. Postoperatively administration of antibiotics was done. Follow up was uneventful. We diagnosed and surgically treated a rare case of Brodies abscess of proximal shaft radius in 17-year-old male. As the upper extremities are areas of unloaded bone, we successfully treated this patient by curettage and antibiotics without bone grafting.